"U-shaped" mesoportal jump graft to manage portal vein thrombosis during liver transplantation: A case report. (2020) - Patrono, Damiano; Salomone, Sara; Guarnaccia, Carla; Tandoi, Francesco; Lupo, Francesco; Fonio, Paolo; Romagnoli, Renato
Highlights: Portal vein thrombosis increases the technical difficulty of liver transplantation. Surgical technique should be adapted to the extent of thrombosis, presence of collaterals and of porto-systemic shunts. In particular cases, a mesoportal jump graft obtained using iliac bifurcation may represent a valuable technical option. Abstract: Introduction: Once considered a contraindication to liver transplantation, portal vein thrombosis still represents a significant challenge to the liver transplant surgeon. Yerdel grade 3 thrombosis is usually managed by interposing a donor iliac vein jump graft between graft portal vein and distal superior mesenteric vein. Venous patch is normally placed in a retrogastric position to avoid its kinking. Presentation of case: We report a new technical variant of standard mesoportal jump graft, in which a U-shaped graft was obtained using iliac bifurcation. This technique was used to manage a case of grade 3 portal vein thrombosis in which portal vein was unsuitable due to severe pylephlebitis and pylorus dissection had to be abandoned due to inflammatory changes issue of chronic pancreatitis. The venous patch was of sufficient length and shape to bypass pancreatic head and first duodenum, avoiding the need for its retrogastric placement and pylorus dissection. Discussion: This case is a further demonstration that technical approach to portal vein thrombosis must be tailored according to its extent and surgical scenario. In selected cases, use of a curved U-shaped jump graft may represent a valuable option. Conclusion: This technical option should be included among options for the management of portal vein thrombosis and be part of the armamentarium of liver transplant surgeon.